PENINGKATAN PRODUKTIVITAS TAMBAK UDANG VANAME MELALUI PENGEMBANGAN SUMBERDAYA MANUSIA DI DESA KARANGSEWU, KECAMATAN GALUR, KABUPATEN KULON PROGO, DIY : Increasing the Productivity of White Shrimp Ponds Through Human Resources Development in Karangsewu Village, Galur District, Kulon Progo Regency, DIY - Diatin, Iis; Budiardi, Tatag; Hadiroseyani, Yani; Effendi, Irzal; Widanarni, Widanarni; Vinasyam, Apriana; Astari, Belinda; Apriani, Ita (Universitas Mataram, 2024)
Quality of human resources is a key factor in the success of cultivation. Farmers who have good technical knowledge and skills tend to be more successful in managing their ponds. Therefore, through training and mentoring programs, it is hoped that the knowledge and skills needed to increase shrimp pond productivity can be provided. The purpose of this activity is to improve farmers' understanding of effective and efficient white shrimp cultivation techniques, identify problems, and create networks between farmers to share experiences and information. The training was held in July 2024 in Karangsewu Village, Galur District, Kulon Progo Regency, D.I.Yogyakarta Province. The training attended by 35 participants consisting of white shrimp farmers, fisheries extension workers, and the surrounding community. After completing the training, participants received support in the form of mentoring for shrimp cultivation activities for three months. Pre-tests and post-tests were conducted to measure the increase in participants' knowledge. The results showed that the level of knowledge of participants increased by 6.64%. As many as 79% of participants strongly agreed that the training could improve their knowledge, 71% strongly agreed that the training they attended was relevant to their jobs, and 86% of participants stated that they could develop their potential after attending the program. The results of post-training monitoring showed that productivity of white shrimp pond increased from an average of 12 tons/ha to 23.16 tons/ha. This program not only increases productivity and business sustainability, but also has a positive impact on the economy of the surrounding community. There needs to be a follow-up program to improve shrimp farmers' understanding of financial management, marketing strategies, and the development of value-added products.